Electrochemical Studies for the Determination of Quetiapine Fumarate and Olanzapine Antipsychotic Drugs - Manal A. El-Shal (Tabriz University of Medical Sciences, 2013)
Purpose: Cyclic voltammetry and differential pulse voltammetry were used to explore the diffusion behavior of two antipsychotic drugs at a glassy carbon electrode. A well-defined oxidation peak was obtained in Britton-Robinson (BR) buffer (pH 2.0). The response was evaluated as a function of some variables such as the scan rate, and pH. Methods: A simple, precise, inexpensive and sensitive voltammetric method has been developed for the determination of the cited drugs Olanzapine (OLZ) and Quetiapine fumarate (QUT). Results: A linear calibration was obtained from 3 × 10-8 M to 4 × 10-6 M and 2 × 10-8 M to 5 × 10-6 M, with R. S. D. were 1.6 % and 1.2 % for OLZ and QUT, respectively. The limit of detection (LOD) was 1 × 10-8 M, while the limit of quantification (LOQ) was 3 × 10-8 M. Conclusion: The method was applied to the determination of investigated drugs in urine and serum samples and dosage forms.